Natal and neonatal teeth: two clinical cases report - Thaisa Cezária TRICHES; Bruna MONDARDO; Rodrigo Henrique Cezário TRICHES; Mabel Mariela Rodríguez Cordeiro; Marcos Antonio da Silva Cristovam (Faculdade São Leopoldo Mandic, 2018)
The aim of this study was to report two cases of newborns with natal and neonatal teeth. Case 1 - a female child presented a natal tooth in the region of lower central incisors since birth. Mother's child reported a family history of this feature. Since the tooth did not present either mobility, prevent breastfeeding, cause discomfort to the child or hurt mother's breast, it was chosen for its maintenance and monitoring. Case 2 - a male child presented, during the first two weeks of life, the eruption of two neonatal teeth in the region of lower central incisors. During the interview, his mother reported no familiar history of this condition. Because the teeth has tapered edges, causing the Riga-Fede's disease, impairing breastfeeding, causing discomfort to the child and injuring the mother's breast, it was decided for its extraction. It may be concluded that the presence of natal and neonatal teeth represent a rare condition that requires further studies to confirm its etiology. Therapeutic approaches must be preceded by a careful clinical evaluation since, as it was seen in this report, both cases were submitted to different treatments showing good evolution.